Mekanisme Stres Oksidatif dan Inflamasi Akibat Paparan Kronis PM2.5 terhadap Penurunan Fungsi Paru di Lingkungan Urban Systematic Review - Zahwa Ramadani; Gita Jazila Arista; Cut Sari Ramadhani; Firdus Firdus; Muhammad Nasir; Alia Rizki (Universitas Syiah Kuala, 2026)
Exposure to fine particulate matter measuring ≤2.5 µm (PM2.5) is one of the environmental issues that significantly impacts respiratory health in urban areas. This article aims to examine the impact of chronic PM2.5 exposure on respiratory health in urban environments. This study employs a systematic literature review method using databases (Google Scholar, the National Library of Indonesia, and electronic resources) with relevant articles indexed over a 10-year period (2016–2026). The review results indicate that PM2.5 exposure is associated with an increased risk of respiratory diseases such as asthma, pneumonia, and COPD, which have a significant impact on vulnerable groups. Various mitigation strategies, such as expanding green spaces, forest conservation, controlling emissions from the transportation sector, and raising industry awareness, have led to a reduction in air pollutant levels. However, these approaches are not the primary solution, as high pollution levels reflect an imbalance between anthropogenic activities and the environment’s capacity for natural purification; therefore, additional mitigation strategies are needed to reduce the impact of PM2.5 on public health and well-being.